Analysis on the overpressure characterization with respect to depositional environment facies: Case Study in Miri Area, Baram Delta - Hanapiah, N.M. (Institute of Physics Publishing, 2017)
Overpressure studies in oil and gas exploration and production are carried out in order to mitigate any losses that could happen while drilling. These concerns can be addressed by enhancing the understanding of overpressure characterization in the fields. This research emphasizes in determining the pore pressure trend in Miri area to assist pore pressure prediction for future hydrocarbon exploration and production. Generally, pore pressure trends are related to mechanisms that contribute to the overpressure generation. In the region predominant overpressure are disequilibrium compaction within the prodelta shales meanwhile in outer shelf overpressure generation controlled by fluid expansion in deltaic sequence of inner shelf area. The objective of this research is to analyze the pore pressure profile of wells for determining vertical trends of pore pressure for various depositional environment facies of Miri area. Integration of rock physics and pore pressure analysis and relating the trends to environment depositional environment facies within shale underlying sand interval. Analysis done shows that overpressure top is characterize by depositional environment facies within shale underlying sand interval. © Published under licence by IOP Publishing Ltd.